Optimized design of layered bridge transducer for piezoelectric energy harvesting from roadway. (15th December 2017) - Jasim, Abbas; Wang, Hao; Yesner, Greg; Safari, Ahmad; Maher, Ali
Abstract: This study aims to develop a novel design of piezoelectric transducer with the optimized geometry that is targeted for energy harvesting in roadway under vehicular loading. The Bridge transducer with layered poling and electrode design is proposed to enhance energy output. Finite element analysis was conducted to predict energy output and stress concentration in the transducer. Multi-physics simulations were conducted to evaluate energy outputs using different lead zirconate titanate materials, loading magnitudes, transducer types, and geometry parameters. The optimum configuration of transducer geometry was evaluated considering the balance between energy harvesting performance and mechanical failure potential due to stress concentrations. The novel design of Bridge transducer with layered poling and electrodes produces much greater energy than the traditional bridge and Cymbal transducer. The results show that within the failure stress criteria, the optimized design of Bridge transducer produced an electrical potential of 556 V, which could result in 0.743 mJ of potential energy (open circuit condition) for a single transducer under the external stress of 0.7 MPa. Laboratory testing on energy harvester module showed that simulation results agreed well with the measured power. Highlights: Developed a novel design of piezoelectric transducer for energy harvesting from roadway. Optimized geometry design for energy harvesting and mechanical stress concentration. Validated power output of energy harvester with laboratory testing.